CONSERVATIVE SOLUTE TRANSPORT FROM SOIL THROUGH OVERLAND FLOW ON STEEP SLOPED AREA - Trisna Kusuma NIM : 25315038, Gilang
Solute transport through overland flow from the soil is the major source of non-point pollution, whereas the overland flow development on steep sloped area is based from the complex and non-linear system that can be caused by infiltration excess, saturation excess, and subsurface flow. A field research using several scenario of rainfall height and landcover conducted to prove the dominant mechanism of the overland flow formation on the steep slope accompanied with conservative matter transport as a function of rainfall intensity, soil characteristics, landcover, and slope. Output of the quantitative model succeeded to prove that the overland flow generation on the steep slope on the field plot is dominated by the saturation excess mechanism, with Natural Grass (NG) plot generating the lowest percentage of overland flow by value of 21,85% and 50,03% for rainfall height of 24,9 mm and 21,8 mm, compared to Cut Grass (CG) with percentage of 61.24% and 81.43% and also Without Grass (WG) plot with 59.47% and 84.57%. Transport model output from rainfall height of 24,9 mm with the addition of salt indicating that the salinity concentration measured on NG and CG plot as the lowest with value of 56,04 and 33,05 ppm, accompanied by the indication of slowest salinity transport that is occurred on the NG plot which started to be counted from the interval of 45-50 minutes after the artificial rainfall was applied.